Preparedness of Public Secondary Schools to Provide a Conducive Social Environment for the Implementation of Re-Entry Circular No. 2 of 2021 In Mwanza Region (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigated preparedness of public secondary schools to provide a conducive social environment for the implementation of re-entry circular no. 2 of 2021 in Mwanza region. A convergent design under mixed research approach was employed. The target population was 216 public secondary schools, 6604 teachers,149936 regular students, 57 re-entry students and 8 District Secondary Educational Officers. The sample size for the study comprised 613 respondents. This included 7 district educational officers, 22 heads of schools, 22 guidance and counselling teachers, 57 re-entry students, 270 regular students, and 235 secondary school teachers. Purposive and stratified simple random sampling techniques were used to obtain the sample. Data were collected through an interview guide, Focus group discussions and questionnaires. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were analysed thematically. The findings indicated that respondents moderately agreed that the school has prepared a conducive environment for the implementation of the re-entry circular and for welcoming back the returning students. The study concludes that the social atmosphere in some public secondary schools is still unwelcoming and unsuitable for the re-entry students. The study recommends that a safe and supportive environment in schools should be promoted to ensure that stigmatisation, exclusion, and bullying of re-entry students is completely addressed in public secondary schools so as to improve implementation of re-entry circular Number two of 2021.